Data from: Untangling the roles of microclimate, behaviour and physiological polymorphism in governing vulnerability of intertidal snails to heat stress - Dong, Yun-wei; Li, Xiao-xu; Choi, Francis M.P.; Williams, Gray A.; Somero, George N.; Helmuth, Brian; Choi, Francis M. P. (Dryad, 2017)
Biogeographic distributions are driven by cumulative effects of smaller
scale processes. Thus, vulnerability of animals to thermal stress is the
result of physiological sensitivities to body temperature (Tb),
microclimatic conditions, and behavioural thermoregulation. To understand
interactions among these variables, we analysed the thermal tolerances of
three species of intertidal snails from different latitudes along the
Chinese coast, and estimated potential Tb in different microhabitats at
each site. We then empirically determined the temperatures at which heart
rate decreased sharply with rising temperature (Arrhenius breakpoint
temperature, ABT) and at which it fell to zero (flat line temperature,
FLT) to calculate thermal safety margins (TSM). Regular exceedance of FLT
in sun-exposed microhabitats, a lethal effect, was predicted for only one
mid-latitude site. However, ABTs of some individuals were exceeded at
sun-exposed microhabitats in most sites, suggesting physiological
impairment for snails with poor behavioural thermoregulation and revealing
inter-individual variations (physiological polymorphism) of thermal
limits. An autocorrelation analysis of Tb showed that predictability of
extreme temperatures was lowest at the hottest sites, indicating that the
effectiveness of behavioural thermoregulation is potentially lowest at
these sites. These results illustrate the critical roles of mechanistic
studies at small spatial scales when predicting effects of climate change.
TPC modelling results for littoraria sinensisResults of thermal
performance curve models using an exponential modified Gaussian model for
Littoraria sinensis along the coast of
ChinaTPC_modelling_results_littoraria_sinensis.txtTPC modelling results
littorina breviculaResults of thermal performance curve models using an
exponential modified Gaussian model for Littorina brevicula along the
coast of ChinaTPC_modelling_results_littorina_brevicula.txtTPC modelling
results Nerita yoldiiResults of thermal performance curve models using an
exponential modified Gaussian model for Nerita yoldii along the coast of
ChinaTPC_modelling_results_nerita_yoldii.txt
Keywords: Physiological adaptation; heat budget model; microhabitat